DESIGN AND CONSTRUCTION OF MIXER WITH VARIABLE SPEED FOR MANUFACTURING NANOPARTICLE COMPOSITE MATERIALS - Michael Rivaldo Simanjorang; Heru Susanto; Muhammad Luqman Bukhori (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2022)
Variable speed mixer machine is a tool to help stir and mix resin with nanoparticles, design and build of the mixer plan the design of the variable speed mixer which aims to make the resin viscosity more evenly distributed in the manufacture of composites and determine the performance of the equipment produced by the variable speed mixer. This is because in manual mixing the mixed materials such as resin nanoparticles have not been mixed evenly or homogeneously. This mixer design tool can be used as a basis for developing work in the field of composite mixing, problems in composite manufacturing include; resin flow control and how to prevent the occurrence of white spots (white dots in the composite). y designing and using this variable speed mixer machine, the results of designing a mixer image with variable speed control using solid works software is the first step in working on a mixer design with variable speed control, after having data in the form of design drawings, a product design in the form of a mixer with variable speed is obtained. . speed control. It is known that the specifications of the mixer with variable speed for composites and nanoparticles are known, it is known that the working principle of a mixer with variable speed control for composites and nanoparticles can make the viscosity mixed more evenly. because the stirring speed regulated by the speed control has a constant speed. The results of testing the mixer machine with speed control, namely the motor can work according to the design plan, where the motor can produce rotation with the required variations and can be adjusted as needed.